Clinical trial for the control of water intake of patients undergoing hemodialysis treatment - Oller, Graziella Allana Serra Alves de Oliveira (Escola de Enfermagem de Ribeirão Preto / Universidade de São Paulo, 2018)

(untitled) (Rev Lat Am Enfermagem)
OBJECTIVE: to analyze the impact of an educational and motivational intervention for patients with a chronic kidney disease, undergoing hemodialysis treatment, on the control of fluid intake during interdialytic periods. METHOD: a quasi-experimental, non-randomized clinical trial with patients from a Nephrological Unit of the State of São Paulo. Participants were included in two groups: Control Group with 106 patients and Intervention Group with 86 patients, totaling 192 participants. The used intervention was an educational and motivational video to control liquid intake, based on the Bandura’s Theory. The measure of control of water intake was the percentage of lost weight, also considered the variable outcome of the research. For the data analysis, descriptive analyses and regression analysis of the Inflated Beta Model were used. RESULTS: patients who participated in the intervention had a decrease in the pattern of weight gain in interdialytic periods, with a 3.54 times more chance of reaching the goal of 100% of weight loss when compared to participants from the control group. CONCLUSION: the educational and motivational intervention was effective in reducing the percentage of weight loss in patients undergoing hemodialysis. Brazilian Clinical Trials Registry (ReBEC) under the opinion RBR-4XYTP6.